Integrating RAPFISH-MDS diagnostics into an operational sustainability roadmap for a tropical oxbow lake (Sepunjung, Indonesia) - RIDWAN MANDA PUTRA; TENGKU SAID RAZA’I; SUKENDI SUKENDI; BUDIJONO BUDIJONO; ROMIE JHONNERIE; RONAL KURNIAWAN; EKA PUTRA RAMDHANI; HILFI PARDI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Putra RM, Raza’i TS, Sukendi, Budijono, Jhonnerie R, Kurniawan R, Ramdhani EP, Pardi H. 2026. Integrating RAPFISH-MDS diagnostics into an operational sustainability roadmap for a tropical oxbow lake (Sepunjung, Indonesia). Biodiversitas 27 (3): d270308. https://doi.org/10.13057/biodiv/d270308. Sepunjung Oxbow Lake in Riau Province, Indonesia, is a tropical floodplain lake exposed to increasing ecological and socio-institutional pressures, creating an urgent need for a practical sustainability management framework. This study aimed to develop an operational sustainability roadmap for the lake by integrating biophysical evidence and stakeholder knowledge through Rapid Appraisal for Fisheries with multidimensional scaling (RAPFISH-MDS). Sustainability was assessed across five dimensions using 45 attributes supported by monthly water-quality monitoring from September 2024 to February 2025, fish community observations, field verification, and semi-structured interviews with resource users and relevant stakeholders. The analysis showed that the ecological dimension had the lowest sustainability index (31.8), followed by legal-institutional (43.2), while the economic (52.3), technological (55.9), and socio-cultural (59.0) dimensions were classified as moderately sustainable. Monte Carlo testing confirmed the stability of the ordination results. Sensitivity analysis identified key leverage attributes, and Pareto screening selected 13 priority factors explaining 78.2% of total sensitivity. The most critical intervention areas were aquatic vegetation cover, water quality, riparian forest condition, utilization zoning, community empowerment, monitoring facilities, and fishery product marketing. Based on these findings, a 12-24 month operational roadmap is proposed, focusing on ecological rehabilitation, participatory fisheries control, institutional strengthening, and livelihood improvement. The study demonstrates that multidimensional sustainability diagnostics can be translated into concrete management priorities for tropical oxbow lakes in Indonesia.